Is the QBS-ar index a good tool to detect the soil quality in Mediterranean areas? A cork tree Quercus suber L. (Fagaceae) wood as a case of study - Galli, L.; Capurro, M.; Menta, C.; Rellini, I. (Italian Journal of Zoology, 2014)
Abstract Cork oak (Quercus suber L., 1753) is a Mediterranean evergreen tree species with a thick and characteristic bark covering the trunk and branches. Despite the fact that cork oak is distributed over about 1.7 million hectares in the western Mediterranean Basin, information about soil biota in this particular habitat at present is scanty. This study was carried out in a cork tree wood in Bergeggi (Liguria, NW Italy), characterized by a Pluvioseasonal Oceanic Mediterranean bioclimate. The profile, texture, pH, total carbonate content, total organic carbon (C) and nitrogen (N) contents, soluble phosphorus (P) and cation exchange capacity were measured in order to characterize the soil. Soil biological quality was evaluated by studying microarthropod communities. Each month, from February 2007 to January 2008, 10 soil samples measuring 10 ? 10 ? 10 cm were collected from the wood being studied and arthropods were extracted using Berlese-Tullgren funnels. The biological quality of soil based on arthropods (QBS-ar) index, taxa abundance, Shannon diversity index (H?) and Pielou?s evenness index (J) were applied to assess soil biological quality in the cork oak being studied. A total of 29 taxonomic groups were identified. Some important groups, such as Pseudoscorpionida, Palpigradi, Miriapoda and Protura were detected every month, but only a few groups showed a clear abundance distribution trend throughout the year and globally it was impossible to define general trends. The results suggested that the condition of the soil was good, as generally observed in natural environments not subjected to significant impacts. It was also possible to demonstrate that the Mediterranean climate causes strong seasonal fluctuations in soil biota, resulting in corresponding differences in the QBS-ar index values. Therefore, the QBS-ar index could be considered to be a valid candidate for the biomonitoring of soil biodiversity in natural and anthropic soils, but in Mediterranean climates comparisons of different areas must be performed analyzing samples collected during the same period.
From Duplicate 2 (Is the QBS-ar index a good tool to detect the soil quality in Mediterranean areas? A cork tree Quercus suber L. (Fagaceae) wood as a case of study - Galli, L; Capurro, M; Menta, C; Rellini, I)From Duplicate 2 (Is the QBS-ar index a good tool to detect the soil quality in Mediterranean areas? A cork tree Quercus suber L. (Fagaceae) wood as a case of study - Galli, L; Capurro, M; Menta, C; Rellini, I)The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Biological index; Cork Oak Forest; microarthropods; QBS-ar; soil quality

Soil microarthropod communities from Mediterranean forest ecosystems in Central Italy under different disturbances. - Blasi, Silvia; Menta, Cristina; Balducci, Lorena; Conti, Federica Delia; Petrini, Enrico; Piovesan, Gianluca (Environmental monitoring and assessment, 2012)
The aim of this study is to assess soil quality in Mediterranean forests of Central Italy, from evergreen to deciduous, with different types of management (coppice vs. high forest vs. secondary old growth) and compaction impacts (machinery vs. recreational). Soil quality was evaluated studying soil microarthropod communities and applying a biological index (QBS-ar) based on the concept that the higher is the soil quality, the higher will be the number of microarthropod groups well adapted to the soil habitat. Our results confirm that hardwood soils are characterised by the highest biodiversity level among terrestrial communities and by a well-structured and mature microarthropod community, which is typical of stable ecosystems (QBS value, >200). While silvicultural practices and forest composition do not seem to influence QBS-ar values or microarthropod community structure, the index is very efficient in detecting soil impacts (soil compaction due to logging activities). Several taxa (Protura, Diplura, Coleoptera adults, Pauropoda, Diplopoda, Symphyla, Chilopoda, Diptera larvae and Opiliones) react negatively to soil compaction and degradation (QBS value, <150). In particular, Protura, Diplura, Symphyla and Pauropoda, are taxonomic groups linked to undisturbed soil. This index could also be a useful tool in monitoring soil biodiversity in protected areas and in urban forestry to prevent the negative effects of trampling. QBS-ar is a candidate index for biomonitoring of soil microarthropod biodiversity across the landscape to provide guidance for the sustainable management of renewable resource and nature conservation.
The following values have no corresponding Zotero field: accession-num: 22585401
Keywords: Biological index; Forest management; microarthropods; Soil disturbance; Soil fauna; Soil monitoring

Decomposition of the organic matter in two forest ecosystems (Natural Park of Montseny, Spain) - I. Abundance, biomass and distribution of the soil microarthropods - Andres, P; Athias-Binche, F (VIE ET MILIEU-LIFE AND ENVIRONMENT, 1998)
This paper represents the first part of a larger work concerning the importance of the oribatid mites in the edaphic trophic chains of two forests (holm-oak and beech woods) under Mediterranean conditions. We offer here the data relating to annual changes of abundance, biomass and vertical distribution of the mesofauna sorted according taxonomic and trophic criteria. The soil was divided into three layers : fresh fallen leaves (L), fermentation layer (F) and organic horizon (S). Rate of leaf imput, dynamics of decomposition, environmental trophic supply, physical structure of the soil and seasonal drought constitute the factors determining the richness and the spatial arrangement of the fauna.
Keywords: decomposition; green oak woodlands; microarthropods; Soil

Decomposition of the organic matter in two forest ecosystems (Natural Park of Montseny, Spain) - I. Abundance, biomass and distribution of the soil microarthropods - Andres, P.; Athias-Binche, F. (VIE ET MILIEU-LIFE AND ENVIRONMENT, 1998)
This paper represents the first part of a larger work concerning the importance of the oribatid mites in the edaphic trophic chains of two forests (holm-oak and beech woods) under Mediterranean conditions. We offer here the data relating to annual changes of abundance, biomass and vertical distribution of the mesofauna sorted according taxonomic and trophic criteria. The soil was divided into three layers : fresh fallen leaves (L), fermentation layer (F) and organic horizon (S). Rate of leaf imput, dynamics of decomposition, environmental trophic supply, physical structure of the soil and seasonal drought constitute the factors determining the richness and the spatial arrangement of the fauna.
The following values have no corresponding Zotero field: pub-location: LABORATOIRE ARAGO, BP 44, 66651 BANYULS-SUR-MER CEDEX, FRANCE publisher: OBSERVATOIRE OCEANOLOGIQUE BANYULS
Keywords: decomposition; green oak woodlands; microarthropods; Soil

IMPACT OF CHRONIC GAMMA-IRRADIATION ON THE LITTER DECAY OF A MIXED MEDITERRANEAN FOREST IN CADARACHE - FRANCE MICROARTHROPODS RESPONSE - POINSOTBALAGUER, N; TABONE, E (PEDOBIOLOGIA, 1995)
An area of mixed forest containing white oak (Quercus pubescens W.) and evergreen oak (Quercus ilex L.) in Cadarache has been irradiated for 16 years, since 1969, by a 137 cesium source of 31.45 TBq. Mass loss of experimental litter over a period of 22 months and its recolonization by soil microarthropods was studied at five stations receiving decreasing radiation levels (100 mGy/h(-1) to 0.3 mGy/h(-1)) and in a control area. At the end of the experimentation, the mass loss of the litter was substantially lower in the three most irradiated stations. Additionally recolonization of litter by microarthropods was low in these three stations compared with the three others. Population density of Oribatids, `'other Acarina'', Collembola and various Arthropods, was considerably lower. These results were dependant upon direct and indirect consequences of irradiation on the ecosystem. Destruction of trees and shrubs in the most irradiated areas (100-60 mGy/h(-1)) did in fact lead to the reduction of soil moisture and an absence of organic matter input. Microflora could not develop and insufficient trophic resources did not allow for recolonization by fauna, which in turn slowed down the eventual disappearance of the litter.
Keywords: CHRONIC GAMMA IRRADIATION; microarthropods; mixed forest